2014
DOI: 10.1038/jcbfm.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling Characterization of Cerebral Perfusion during Normal Maturation from Late Childhood into Adulthood: Normal ‘Reference Range’ Values and Their Use in Clinical Studies

Abstract: The human brain changes structurally and functionally during adolescence, with associated alterations in cerebral perfusion. We performed dynamic arterial spin labeling (ASL) magnetic resonance imaging in healthy subjects between 8 and 32 years of age, to investigate changes in cerebral hemodynamics during normal development. In addition, an inversion recovery sequence allowed quantification of changes in longitudinal relaxation time (T1) and equilibrium longitudinal magnetization (M0). We present mean and ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…Current guidelines state that those children should be transfused indefinitely [47], but the TCD with transfusions changing to hydroxyurea (TWiTCH) trial suggests that, for those with no MRA abnormality may be able to switch to hydroxyurea prophylaxis after a year of transfusion [48]. Hydroxyurea does appear to reduce TCD velocities even without prior blood transfusion [1]; so, in settings where TCD is available but blood transfusion is not possible or is considered hazardous, it is probably reasonable to start hydroxyurea while the results of controlled trials are awaited [49]. In adults with SCD, there are no validated methods to screen for the increased stroke risk, as TCD studies in adults with HbSS find lower velocities than in children and cannot accurately stratify the risk of stroke [50].…”
Section: Primary and Secondary Stroke Preventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current guidelines state that those children should be transfused indefinitely [47], but the TCD with transfusions changing to hydroxyurea (TWiTCH) trial suggests that, for those with no MRA abnormality may be able to switch to hydroxyurea prophylaxis after a year of transfusion [48]. Hydroxyurea does appear to reduce TCD velocities even without prior blood transfusion [1]; so, in settings where TCD is available but blood transfusion is not possible or is considered hazardous, it is probably reasonable to start hydroxyurea while the results of controlled trials are awaited [49]. In adults with SCD, there are no validated methods to screen for the increased stroke risk, as TCD studies in adults with HbSS find lower velocities than in children and cannot accurately stratify the risk of stroke [50].…”
Section: Primary and Secondary Stroke Preventionmentioning
confidence: 99%
“…A French study showed incidence of SCI as 28.2% by 8 years and 37.4% by 14 years [66]. Although it was thought that rates plateau in childhood, there is now evidence of new SCI in older adolescence and adulthood [1,67]. In the London cohort followed from the mid-1990s [68], 30% (3/10 patients) were found to have new SCI after the age of 14, 17 and 21 years, respectively (Figures 2 and 3).…”
Section: Progression Of Scimentioning
confidence: 99%
See 3 more Smart Citations